Optimización de la gestión de órdenes de preparados magistrales en hospitales aplicando tecnologías de información - León Osorio, Gabriel J. (2024)
Medications are a fundamental part of patient care at all stages of their treatment. Magisterial preparations, which are a pharmaceutical product to meet a patient's medical prescription, require adequate management to provide individual safety, which makes it necessary to guarantee that the records corresponding to the production process are reliable and allow their traceability in the attention. The application of information technologies has shown a reduction in medication errors and adverse drug reactions, an impact that has also been documented in electronic prescription. In this study, the steps for the development and implementation of a technological tool through the application of elements of the SCRUM methodology, which allowed optimizing the process of managing medical orders for master mixtures, in a highly complex hospital. reducing times and reducing the risk of errors in the process. The number of orders received that required transcription decreased by 55%, from 2,219 to 999. The batch record consolidation time went from 6 hours to one.